7th Japan Bioanalysis Forum symposium: regulated bioanalysis, to a new stage. (October 2016) - Nakamura, Takahiro
Tower Hall Funabori, Tokyo, Japan, 9–10 March 2016 At the 7th Japan Bioanalysis Forum symposium, bioanalytical methods and processes were discussed with authorities after the issuing of bioanalytical method validation guidelines (EMA and Japanese Ministry of Health, Labour and Welfare) and draft guidance (US FDA). Method establishment and bioanalysis of biomarkers were discussed with a focus on scientific validation. Bioanalytical methods for antibody-drug conjugates, the potential of MS imaging and microsampling activity in drug development were introduced. Discussion groups presented and openly discussed their results with about 300 attendees. This manuscript provides an overview of the highlights of the symposium.